Tribocorrosion research of NI-Al₂O₃/TIO₂ composite materials obtained by the method of electrochemical deposition - Kunitsyn, M. V.; Usov, A. V. (НТУ "ХПІ", 2017)
The purpose of this study was to perform electrochemical deposition and tribocorrosion studies of composite materials based on NI-Al₂O₃/TIO₂. During the research, electrochemical deposition of various composite materials was carried out, while comparison was made with base materials such as duplex steel and electrochemically precipitated nickel. Working particles were characterized using laser dispersion methods and the deposits were characterized by SEM using different detectors (backscattered and secondary electrons), EDX (energy-dispersive x-ray spectroscopy) and FIB (focused ion beam). Based on the photographs taken in SEM, the dependence of the amount of particles in the coating on the concentration of TiO₂ particles in the solution and the time of electrochemical deposition of the coatings was determined. Tribological studies of Steel/Ni/Ni-TiO₂ materials, tribocorrosion studies of Ni/Ni-TiO₂ materials, comparative construction of track profiles obtained by optical method based on confocal microscopy and determination of the height and width of profiles from the material used were also carried out.

Метою даного дослідження було проведення електрохімічного осадження і трібокоррозіонних досліджень композитних матеріалів на основі NI-Al₂O₃/TIO₂. За час досліджень було виконано електрохімічне осадження різних композитних матеріалів, при цьому проводилося порівняння з базовими матеріалами, такими як дуплексна сталь і електрохімічно осаджений нікель. Були охарактеризовані робочі частки з використанням методів лазерної дисперсії, а покриття характеризувалися в SEM з використанням різних детекторів (Зворотне розсіювання і Вторинні електрони), EDX (енергодісперсная рентгенівська спектроскопія) і FIB (сфокусований іонний пучок). На основі виконаних знімків в SEM була визначена залежність кількості частинок в покритті від концентрації частинок TiO₂ в розчині і часу електрохімічного осадження покриттів. Також були проведені трибологічне дослідження матеріалів Сталь/Ni/Ni-TiO₂, трібокоррозіонне дослідження матеріалів Ni/Ni-TiO₂, порівняльна побудова профілів доріжок отриманих оптичним методом на основі конфокальної мікроскопії та визначення залежності висоти і ширини профілів від використовуваного матеріалу.
Keywords: tribological studies; ferritic-austenitic stainless steel; electrochemical deposition; track profiles; композитні матеріали; трибологічні дослідження матеріалів